An Approximate Solution of Higher Order Ordinary Differential Equations Using Modified Adomian Decomposition Method - Nuha Mohammed Dabwan; Yahya Qaid Hasan (IJRDO -JOURNAL OF MATHEMATICS, 2020)
Modified Adomian Decomposition Method (MADM) is used in this article to solve higher order ordinary differential equations. Some examples are proposed to show the ability of the methed for solving this type of equations.